Minimum cement volume required in vertebral body augmentation—A biomechanical study comparing the permanent SpineJack device and balloon kyphoplasty in traumatic fracture. Issue 7 (August 2015) - Rotter, Robert; Schmitt, Lena; Gierer, Philip; Schmitz, Klaus-Peter; Noriega, David; Mittlmeier, Thomas; Meeder, Peter-J.; Martin, Heiner
Abstract: Background : Minimally invasive treatment of vertebral fractures is basically characterized by cement augmentation. Using the combination of a permanent implant plus cement, it is now conceivable that the amount of cement can be reduced and so this augmentation could be an attractive opportunity for use in traumatic fractures in young and middle-aged patients. The objective of this study was to determine the smallest volume of cement necessary to stabilize fractured vertebrae comparing the SpineJack system to the gold standard, balloon kyphoplasty. Methods : 36 fresh frozen human cadaveric vertebral bodies (T11-L3) were utilized. After creating typical compression wedge fractures (AO A1.2.1), the vertebral bodies were reduced by SpineJack (n = 18) or kyphoplasty (n = 18) under preload (100 N). Subsequently, different amounts of bone cement (10%, 16% or 30% of the vertebral body volume) were inserted. Finally, static and dynamic biomechanical tests were performed. Findings : Following augmentation and fatigue tests, vertebrae treated with SpineJack did not show any significant loss of intraoperative height gain, in contrast to kyphoplasty. In the 10% and 16%-group the height restoration expressed as a percentage of the initial height was significantly increased with the SpineJack (> 300%). Intraoperative SpineJack could preserve the maximum height gain (mean 1% height loss) better than kyphoplasty (mean 16% height loss). Interpretation : In traumatic wedge fractures it is possible to reduce the amount of cement to 10% of the vertebral body volume when SpineJack is used without compromising the reposition height after reduction, in contrast to kyphoplasty that needs a 30% cement volume. Highlights: SpineJack did not show any significant loss of intraoperative height gain, in contrast to kyphoplasty. The SpineJack allows the amount of cement to be reduced to 10% of the vertebral body volume. It is impossible to reduce the amount of cement to less than 16% or 30% when using kyphoplasty.